2017
DOI: 10.1016/j.neuroimage.2017.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Imaging neuronal pathways with 52Mn PET: Toxicity evaluation in rats

Abstract: Manganese in its divalent state (Mn 2+ ) has features that make it a unique tool for tracing neuronal pathways. It is taken up and transported by neurons in an activity dependent manner and it can cross synapses. It also acts as a contrast agent for magnetic resonance imaging (MRI) enabling visualization of neuronal tracts. However, due to the limited sensitivity of MRI systems relatively high Mn 2+ doses are required. This is undesirable, especially in long-term studies, because of the known toxicity of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The half-life of 5.6 days, of the positron emitter 52 Mn allows its use in longitudinal biodistribution studies in the body and brain (Topping et al, 2013; Graves et al, 2015; Brunnquell et al, 2016; Hernandez et al, 2017; Napieczynska et al, 2017; Saar et al, 2018). MEMRI studies have shown that following systemic administration, the final distribution of manganese in the brain that allows anatomical structures was achieved 24 h after infusion.…”
Section: Translating Memri To Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…The half-life of 5.6 days, of the positron emitter 52 Mn allows its use in longitudinal biodistribution studies in the body and brain (Topping et al, 2013; Graves et al, 2015; Brunnquell et al, 2016; Hernandez et al, 2017; Napieczynska et al, 2017; Saar et al, 2018). MEMRI studies have shown that following systemic administration, the final distribution of manganese in the brain that allows anatomical structures was achieved 24 h after infusion.…”
Section: Translating Memri To Humansmentioning
confidence: 99%
“…By 4 days later 52 Mn 2+ could be traced to the amygdala and prefrontal areas of the cortex (Figure 2). Nepieczynska et al (Napieczynska et al, 2017) showed imaging of the dopaminergic and striatonigral pathways in rats 24 h after direct injection of 52 Mn 2+ into the ventral tegmental area and the dorsal striatum, respectively. The ability of 52 Mn 2+ to follow neuronal pathways after direct injection of the 52 Mn 2+ PET tracer to a specific area in the brain similar to MEMRI, can be used to study all the neuronal pathways already studied with MEMRI such as the visual and BG pathways (Pautler et al, 1998; Watanabe et al, 2001; Murayama et al, 2006).…”
Section: Translating Memri To Humansmentioning
confidence: 99%
“…Connections to the prefrontal areas could also be detected after a few days. In a recent paper, Mn-52 was used to image the dopaminergic and striatonigral pathways in rats 24 h after tracer injection into the ventral tegmental area and the dorsal striatum, respectively [37]. The ability to follow neuronal connections in the brain following targeted administration of [ 52 Mn]Mn 2+ to a specific area can be expanded to many other neuronal pathways that have been demonstrated with MEMRI, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a renewed interest in using radioactive manganese for PET imaging, in particular manganese-52 [32][33][34][35][36][37]. Mn-52 is a positron emitter with a long halflife of 5.6 days, which allows longitudinal biodistribution studies in the body and brain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors stated that [ 52g Mn]MnCl 2 , although not suitable in this case, still holds promise as a radiotracer for specific uptake in the salivary glands and pancreas. Another publication evaluated 52g Mn for neuroimaging by stereotactic injection into the rat brain . The neuronal pathways between rat brain regions could be imaged successfully.…”
Section: Manganese‐52g In Preclinical Researchmentioning
confidence: 99%